THE MAIN PURPOSE OF CREATING ARTIFICIAL INTELLIGENCE AND ITS ROLE IN SOCIETY (Web of Teachers: Inderscience Research, 2025)
This article provides a detailed exploration of the foundational objectives underlying the creation of artificial intelligence (AI), supported by scientific evidence. It examines the historical origins of AI, shedding light on the motivations of early innovators who sought to emulate human cognitive processes, including reasoning, learning, and decision-making. Their aim was to develop systems capable of efficiently executing complex tasks. Initially, AI technologies were conceived to automate repetitive and labor-intensive processes, thereby enhancing efficiency and reliability. Over time, the applications of AI broadened to address real-world challenges, such as advancing healthcare systems, facilitating global communication, and streamlining industrial operations. The article further elaborates on the core scientific methodologies that shaped AI’s development, including neural networks, machine learning techniques, and sophisticated data-processing frameworks. By simulating human brain functions, AI systems were engineered to process large datasets and deliver precise predictions and solutions.